PRODUKTIVITAS KERJA PEGAWAI YANG DI PENGARUHI OLEH WORK FROM HOME (WFH) DAN LINGKUNGAN KERJA SELAMA MASA PANDEMI PADA DINAS PERHUBUNGAN KOTA BIMA - Al Halim, Rifky; Kusumayadi, Firmansyah (Jurnal Riset Manajemen dan Akuntansi, 2022)
This study aims to determine the partially significant effect of work from home (WHF) on work productivity at the Bima City Transportation Service. To find out the partially significant effect of the work environment on work productivity at the Department of Transportation of the City of Bima. To find out (WHF) and the work environment have a significant simultaneous effect on the work productivity of employees at the Department of Transportation of the City of Bima. The instrument in this study used a questionnaire with a Likert scale. The population in this study were 80 employees consisting of 34 civil servants and 46 honorary employees. The sample in this study were 34 civil servants. The sampling technique used by the researcher was purposive sampling. Data collection techniques using questionnaires, observation and literature studies, data analysis techniques using validity tests, reliability tests, classical assumptions test, multiple linear regression analysis, correlation analysis, coefficient of determination, t test and f test with the help of SPSS. The results showed that Work From Home (WFH) significantly affected employee productivity at the Department of Transportation of the City of Bima, the work environment significantly had an influence on the productivity of employees at the Department of Transportation of the City of Bima, simultaneously the variables (X1) Work From Home (WFH) and the work environment (X2) at the Department of Transportation of the City of Bima has a significant effect on employee work productivity (Y)